Peran Pemerintahan Daerah dalam Pengembangan Ekonomi Kreatif di Kota Malang - Wijaya Syahputra, Rafli Ragil; Hady, Nuruddin (Jurnal Ilmiah Administrasi Publik, 2025)
Malang City focuses economic growth on the creative economy sector, however there is no equity and connectivity of the creative economy sector with one another, so it is necessary to maximize the role of the Malang City Government, The purpose of this study (1) Highlighting the role of the Malang City Government in the development of the creative economy (2) Knowing what are the driving factors and inhibiting factors in the development of the creative economy in Malang City (3) Local Government solutions in creative economic development. This research, using descriptive qualitative methods with qualitative data analysis. The results of the analysis show that the role of Government as (1) Regulator, (2) Catalyst, facilitator and advocate (3) Urban planner is going well while the role of government as (4) Consumer, investor and even entrepreneur needs to be improved. The driving factors of creative economic development are; strengthening the creative and digital economy, the availability of Malang Creative Center, strengthening domestic products and population demographic bonuses while the inhibiting factors of creative economic development are; startup coaching facilities and activation of the management of Malang Creative Center have not been maximized, the difficulty of accessing the creative product market. Conclusion The implementation of the creative economy in Malang City is going quite well, it needs to be improved so that the creative economy is more optimal.